ANALISIS PENERAPAN PSAK 50 DAN 55 ATAS IMPAIRMENT PIUTANG PADA PT. PUTRA KARANGETANG - Akun, Ismie Iswara; Karamoy, Herman; Kalalo, Meily (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
In conducting the sale of goods and services. The sale is made in cash and lending. Receivables arising from the sale or delivery of goods and services on credit are classified as trade receivables which are then not likely to change into receivables. And receivables may decrease in value over time. Research objectives to determine the extent to which the application of PSAK 50 & PSAK 55 on impairment of receivables at PT. Putra Karangetang. The method used is descriptive research method. The result of the research can be concluded that during the last 3 (three) years there has been a decrease in the value of receivables, because PT. Son of Karangetang value of receivable there is a decline in value per year then it will be good for company. For the presentation process, recognition, measurement is in accordance with PSAK 50 & 55 (revised 2014).Keywords : presentation, recognition, measurement, impairment, receivables